Spirodelae Herba ethanol extract attenuates neurotoxicity in hippocampal cells and improves scopolamine-induced cognitive impairment in mice - Jeong, Yun Hee; Jung, YeonGyun; Li, Wei; Yang, Hye Jin; Oh, You-Chang; Bae, Jong-Sup (Frontiers in Pharmacology, 2025)
BackgroundSpirodelae Herba (SH) is an herb that has been used in traditional medicine in East Asia. Whereas its anti-inflammatory, anti-allergic, and antioxidant activities have recently been demonstrated, the effects of SH ethanol extract (SHE) on neurotoxicity in hippocampal neurons, neuroinflammation in microglia, and cognitive impairment in mice have not been studied.MethodsIn this study, we explored the protective effect of SHE on neurotoxicity related to oxidative stress and the related molecular mechanisms in a hippocampal cell model. We also examined the inhibitory effect of SHE on neuroinflammation and its related mechanisms in endotoxin-stimulated microglia. We also explored the ameliorative effect of SHE on cognitive impairment in mice through behavioral tests and examined histopathological changes in the hippocampus and cortex using Nissl staining. In addition, we conducted a comprehensive analysis of the related mechanisms, including the microbiota–gut–brain axis.ResultsSHE inhibited glutamate-induced neurotoxicity in HT22 cells and induced changes in related mechanisms. SHE effectively inhibited lipopolysaccharide-induced neuroinflammation in BV2 cells and regulated the activation of related mechanisms. In addition, SHE administration significantly alleviated scopolamine (SCO)-induced decreases in memory and learning ability in mice. SHE suppressed damage to hippocampal neurons in the mice’s brain and significantly increased the expression of the brain-derived neurotrophic factor and its related pathway proteins in hippocampal tissue. Furthermore, microbiome analysis revealed that SHE administration normalized SCO-induced gut microbiota imbalance (dysbiosis). These findings indicate that the cognitive improvement effects of SHE may be mediated through the modulation of the gut microbiota composition and the microbiota–gut–brain axis.ConclusionThe results of this study demonstrate the neuroprotective and anti-neuroinflammatory effects of SHE and its strong potential as a preventive and therapeutic agent for cognitive impairment.